Breakdown mode and parameter space of micro-discharge sustained by thermionic emission. (16th March 2023) - Li, Xiandi; Wu, Hao; Zhong, Yujie; Guo, Chengzhi; Yi, Lin; Jiang, Wei; Zhang, Ya
Abstract: Gas breakdown driven by thermionic emission in a microgap to produce low-temperature plasma is studied using a 1D implicit particle-in-cell/Monte Carlo collision model. The influence of background gas pressure, external driving voltage, cathode temperature and discharge gap on argon glow micro-discharge in the parallel plate was simulated. Different parameters and conditions have different effects on the gas breakdown at small size. The discharge gap of hundreds of µ m has little influence on the gas breakdown and only changes the plasma distribution. As the applied voltage increases, the gas changes from a non-breakdown mode to a breakdown mode, and the gas breakdown is more sensitive to the applied voltage than the gas pressure at low voltages. In all breakdown modes, the gas pressure hardly changes the plasma evolution characteristics. At appropriate cathode temperatures, the density of electrons and ions increases rapidly, forming a stable sheath, and the equivalent resistance of the discharge gap becomes smaller as the temperature rises and the plasma is in abnormal glow discharge.